EVISITING THE WORKING-OUT AND IMPLEMENTATION OF STRATEGIC PROGRAMS FOR THE DEVELOPMENT OF REGIONAL INDUSTRIAL COMPLEXES - Galina Peshkova; Alexander Kolesnikov (Вестник Северо-Кавказского федерального университета)
The article focuses on the working-out and implementation of strategic policy documents at the level of industries and complexes of the region. It points to the importance of strategic planning and programming of industry development in the region. Analysis of tiered/split-level strategic programming is given. It defines the basic approaches to strategic planning and programming on the example of the industry for the extraction of non-metallic construction materials in Leningrad region. Conclusions are drawn and recommendations for further research are given.